Dynamism the values that drive innovation, job satisfaction, and economic growth - Phelps, Edmund S.; Bojilov, Raicho 1982-; Hoon, Hian Teck; Gylfi Zoega (Cambridge, Massachusetts Harvard University Press, 2020)
"In Dynamism Nobel Laureate Edmund Phelps, Raicho Bojilov, Hian Teck Hoon, and Gylfi Zoega argue that the high level of innovation in the West was not a result of scientific discoveries plus entrepreneurship. Rather, modern values-particularly the individualism and self-expression prevailing among the people-fueled the dynamism needed for widespread innovation"--Provided by publisher.
Introduction: a theory of innovation, flourishing, and growth / Edmund S. Phelps -- Overview of the chapters / Raicho Bojilov, Gylfi Zoega, and Hian Teck Hoon -- I. Estimating innovation - across time and across nations: Innovation - the source of rapid growth / Raicho Bojilov -- Sources of indigenous innovation and channels of its transmission across countries / Raicho Bojilov -- Indigenous innovation during the IT revolution - we never had it so good? / Raicho Bojilov -- II. The roots and benefits of innovation: A case study of Iceland's successful innovators / Gylfi Zoega -- The force of values / Gylfi Zoega -- Individual values, entrepreneurship, and innovation / Raicho Bojilov -- Innovation, job satisfaction, and performance in Western European countries / Gylfi Zoega -- III. Two applications of robots: Growth effects of additive and multiplicative robots alongside conventional machines / Hian Teck Hoon -- Wage effects of additive and multiplicative robots alongside factory buildings and physical structures / Hian Teck Hoon -- Additive robots, relative prices, and indigenous innovation / Hian Teck Hoon.
Includes bibliographical references and index.
Keywords: Technological innovations; Entrepreneurship; Job satisfaction; Individualism; Economic development